EFEKTIVITAS PEMBELAJARAN TEMATIK DALAM MENINGKATKAN KOMPETENSI LITERASI SISWA SEKOLAH DASAR: SEBUAH TINJAUAN LITERATUR - Ainun naim; Denna Anatasya Ukhtifilla; Sawitri Rahmawati; Nabila Hafsah; Tasya Ayu Agustina; Dea Mustika (STKIP Subang, 2025)
This study aims to examine the effectiveness of thematic learning in improving literacy competencies of primary school students through a literature review approach. Basic literacy includes reading, writing, visual and digital skills, which are important foundations in the learning process and cognitive development of children. Using a descriptive-qualitative literature study method, data were collected from relevant SINTA-accredited national journals published between 2018 and 2025. The results of the analysis show that thematic learning can significantly improve students' literacy skills through contextual, integrative and experiential approaches. Factors supporting the success of thematic learning include the active role of teachers, relevant learning media, curriculum flexibility and student participation. However, its implementation still faces a number of challenges such as time constraints, infrastructure and lack of teacher training. These findings emphasize the importance of strengthening teacher training and providing learning resources that support the optimal implementation of thematic learning to improve students' literacy in a sustainable manner.